Defined Microenvironments Trigger In Vitro Gastrulation in Human Pluripotent Stem Cells. Issue 5 (15th December 2022) - Srivastava, Pallavi; Romanazzo, Sara; Kopecky, Chantal; Nemec, Stephanie; Ireland, Jake; Molley, Thomas G.; Lin, Kang; Jayathilaka, Pavithra B.; Pandzic, Elvis; Yeola, Avani; Chandrakanthan, Vashe; Pimanda, John; et al.
Abstract: Gastrulation is a stage in embryo development where three germ layers arise to dictate the human body plan. In vitro models of gastrulation have been demonstrated by treating pluripotent stem cells with soluble morphogens to trigger differentiation. However, in vivo gastrulation is a multistage process coordinated through feedback between soluble gradients and biophysical forces, with the multipotent epiblast transforming to the primitive streak followed by germ layer segregation. Here, the authors show how constraining pluripotent stem cells to hydrogel islands triggers morphogenesis that mirrors the stages preceding in vivo gastrulation, without the need for exogenous supplements. Within hours of initial seeding, cells display a contractile phenotype at the boundary, which leads to enhanced proliferation, yes‐associated protein (YAP) translocation, epithelial to mesenchymal transition, and emergence of SRY‐box transcription factor 17 (SOX17) + T/BRACHYURY + cells. Molecular profiling and pathway analysis reveals a role for mechanotransduction‐coupled wingless‐type (WNT) signaling in orchestrating differentiation, which bears similarities to processes observed in whole organism models of development. After two days, the colonies form multilayered aggregates, which can be removed for further growth and differentiation. This approach demonstrates how materials alone can initiate gastrulation, thereby providing in vitro models of development and a tool to support organoid bioengineering efforts. Abstract : Confining pluripotent stem cells to hydrogel islands initiates epithelial to mesenchymal transition and formation of a primitive streak‐like population, without the addition of soluble triggers. The materials directed morphogenesis is a result of mechanotransduction and wingless type (WNT) signaling, which bears similarities to in vivo models of gastrulation.